Health Care from Patients' Perspective - Glässel, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This IJERPH special issue on "Health Care from the Patient's Perspective" focuses on the perspective of patients as experts, on their challenges and experiences with health care, embedded in a biopsychosocial framework. In doing so, the special issue offers contributions across the entire health and disease continuum from health promotion to rehabilitation and to the outpatient setting described from different perspectives on disease-related situations such as Parkinson's disease, stroke, or multiple sclerosis, diabetes mellitus, and others, to methodological highlights, with a focus on qualitative, but also participatory research as well as quantitative approaches. Experiential research forms the core of this issue. They will not only provide insights into complex health care situations and ethical issues, but also highlight patient-centered problems as a possible starting point for health system and/or policy improvement. It will also take an interprofessional perspective on patients' care providers, family members, or caregivers. We received 19 impressive and important contributions to healthcare that we encourage you to read.